Phakic Cystoid Macular Edema Secondary to Idiopathic Macular Telangiectasia Type 1 Responsive to Topical Anti-Inflammatory Agents*. (March 2013) - Dunn, Evan N.; Gregori, Ninel Z.; Goldhardt, Raquel
ABSTRACT: Purpose : To report a 65-year-old male patient with bilateral phakic cystoid macular edema secondary to idiopathic macular telangiectasia type 1, with robust response to topical steroidal and non-steroidal agents. Methods : Retrospective interventional case report. Chart review. Results : Snellen visual acuity was 20/40 bilaterally. Color fundus photographs showing golden crystalline deposits temporal to the fovea; fluorescein angiography demonstrating telangiectasias with late leakage; and spectral-domain optical coherence tomography revealing intraretinal and subretinal fluid demonstrated findings consistent with idiopathic macular telangiectasia type 1 with bilateral cystoid macular edema. The patient was treated with steroidal and non-steroidal anti-inflammatory drops with complete resolution of edema within two months and improved visual acuity. Over the next two years, edema recurred whenever the drops were stopped and disappeared with reinstitution of topical therapy. Conclusion : Topical steroidal and non-steroidal anti-inflammatory agents may lead to long-term resolution of cystoid macular edema secondary to idiopathic macular telangiectasia type 1.